Performance Measurement System: Management Accounting Information System And Total Quality Management - Siti Mudawanah; Paniran (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2026)
A performance measurement system is the ability for companies to measure how well employees and managers are performing well in meeting current standards and improving every time. In addition, to evaluate employees, a performance measurement system can also develop and motivate employees. The purpose of this study is to determine the influence of Management Accounting Information System and Total Quality Management on the Performance Measurement System in the Production Department of PT. Aplus Pacific for the 2024 period. The hypothesis in this study is suspected to be the Influence of Broad Scope, Employee Involvement and Teamwork. This study uses a quantitative method using primary data through the distribution of questionnaires. The population and this research is the company PT. Aplus Pacific. Sampling used saturated sampling with a total of 53 respondents. The data analysis techniques used in this study used validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, autocorrelation tests, classical assumption tests, multiple linear regression analysis tests, correlation coefficient tests, determination coefficient tests, partial tests and simultaneous tests supported by the IBM SPSSS Statistics Version 20 program. The results of this study show that (1) Partially Broad Scope has a significant effect on Quality. (2) Partially, Employee Involvement Does Not Have a Significant Effect on Quality (3) Partially, Teamwork Does Not Have a Significant Effect on Quality (4) Simultaneously Broad Scope, Employee Involvement, and Teamwork Have a Significant Effect on Quality in the Production Department of PT. Aplus Pacific for the 2024 period. With this research, companies are advised to continue to expand the scope of their projects, but still pay attention to existing resources. And it is necessary to conduct further analysis regarding the type of new projects that have the potential to improve quality and the company needs to maintain and increase sales, streamline costs and develop new products in order to improve quality.